Upaya Meningkatkan Hasil Belajar Materi Wujud Zat Dan Perubahannya Melalui Media Pembelajaran Canva Kelas IV SD Generasi Bangsa Kota Kupang - Jesika Teuf, Melfi; Antonius Suban Hali; Netty E.A Nawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted in two cycles. The subject of the research was fourth grade students of Generasi Bangsa Elementary School with a total of 31 people consisting of 12 boys and 19 girls. The data collection techniques used in this study were observation and test techniques. The results showed an increase in cycle I from a total of 31 students who completed 13 people with a percentage of completeness of 41.93% while 18 students who did not complete with a percentage of unfinished 58.06%. In cycle II, the number of students who completed 25 people with a percentage of 80.63% while students who did not complete 6 people with a percentage of 19.35% unsuccessful. Based on the results of the research above, learning about the form of substances and their changes through canva learning media can improve student learning outcomes, this is evidenced by the increase in the maximum value of completeness yes.